2015
DOI: 10.1063/1.4931461
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide mid-infrared photodetector at 300 K

Abstract: We report on uncooled mid-infrared photovoltaic responses at 300 K arising in heterojunctions of reduced graphene oxide with p-Si. Two major photoresponse spectral peaks are observed, one in the near infrared starting at 1.1 μm corresponding to electron-hole pair generation in the Si substrate, and another at wavelengths below 2.5 μm, arising from properties of the reduced graphene oxide-Si heterojunction. Our analysis of the current-voltage characteristics at various temperatures suggests that the two materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The Tzolov work reported an EQE response in the mid‐IR (2–20 µm) and suggested that this may be due to a contribution to the photocurrent from the tubular carbon material in their study. However, it seems more likely that this was due to the free carrier response of the silicon as also observed in a recent work from the same research group using reduced graphene oxide/ p ‐Si photodetectors . Likewise, the Ong work observed a shoulder on the IR side of the photocurrent spectrum which was suggested to be due to the nanotubes, but could also be due to a contribution from the silicon rear junction .…”
Section: Introductionmentioning
confidence: 53%
“…The Tzolov work reported an EQE response in the mid‐IR (2–20 µm) and suggested that this may be due to a contribution to the photocurrent from the tubular carbon material in their study. However, it seems more likely that this was due to the free carrier response of the silicon as also observed in a recent work from the same research group using reduced graphene oxide/ p ‐Si photodetectors . Likewise, the Ong work observed a shoulder on the IR side of the photocurrent spectrum which was suggested to be due to the nanotubes, but could also be due to a contribution from the silicon rear junction .…”
Section: Introductionmentioning
confidence: 53%
“…In most cases, the responsivity of graphene or RGO is in range of few mA.W -1 or less. [13,14,42,[54][55][56][57][58][59][60][61][62] Due to poor absorption and fast carrier recombination, EQE is very low for monolayer or very few layer graphene based photodetector. The responsivity and EQE values of our RGOs are comparable with the graphene nano-ribbon as an active material.…”
Section: Methodsmentioning
confidence: 99%
“… 97 Unlike single walled carbon nanotubes (SWCNT), which is having strong wavelength dependent spectra, GO generally respond to almost all the wavelength due to its wide absorption range 98 ; Thus, rGO-based photodetectors generally show photo detection from UV 97 , 99 to IR. 100 , 101 , 102 , 103 In rGO-based photodetectors, it is generally observed that the photo current depends on the photo illumination position owing to the locally generated electric field via the Schottky barrier. 104 , 105 , 106 Even though, there are photodetectors based on TMDs, compared to graphene it is still in its infancy stage.…”
Section: Applications Of 2d Materials In Both the Academic And Indust...mentioning
confidence: 99%